1998
DOI: 10.1007/bf03028805
|View full text |Cite
|
Sign up to set email alerts
|

Central motor conduction after magnetic stimulation in diabetes

Abstract: Central motor conduction times (CMCTs), obtained by means of magnetic stimulation of the motor cortex and spinal roots, were studied in 138 patients affected by diabetes mellitus but with no signs or symptoms of central nervous system (CNS) involvement. CMCTs were significantly increased in diabetic patients (p < 0.001, t-test) with respect to normal controls, with values exceeding upper confidence limits (mean +/- 2.5 SD of controls) in about 30% of patients. There was no correlation between CMCT delay and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…We report that a short duration (8 weeks) of sustained hyperglycemia/hypoinsulinemia produced a marked attenuation of cerebral corticalϪevoked forelimb motor responses with a significant reduction of motor area topography. This novel finding is consistent with previous reports of decreased hippocampal synaptic plasticity (19,20) and disruption of neuronal function (6,7,21,22) in diabetes. This study extends these observations and suggests that dysregulation of central glucose and insulin in patients with poorly controlled diabetes may result in altered cerebral corticospinal motor function.…”
supporting
confidence: 93%
“…We report that a short duration (8 weeks) of sustained hyperglycemia/hypoinsulinemia produced a marked attenuation of cerebral corticalϪevoked forelimb motor responses with a significant reduction of motor area topography. This novel finding is consistent with previous reports of decreased hippocampal synaptic plasticity (19,20) and disruption of neuronal function (6,7,21,22) in diabetes. This study extends these observations and suggests that dysregulation of central glucose and insulin in patients with poorly controlled diabetes may result in altered cerebral corticospinal motor function.…”
supporting
confidence: 93%
“…For descending corticospinal projections from M1, diffusion tensor imaging studies report decreases in microstructural integrity in the descending white matter of the CST (27)(28)(29)(30)(31), which relates to cortical atrophy in M1 (2). The conduction velocity of upper motor neurons of the CST is delayed in humans (32,33) and in rodent models of diabetes (34). Loss of microstructural integrity and delays in conduction velocity are indicative of neuronal loss or demyelination in this critical motor pathway.…”
Section: Somatosensory and Motor Cortexmentioning
confidence: 99%
“…The study shows that central conduction time was significantly increased in diabetic subjects. 12 Toppish demonstrated that patients with diabetes mellitus had a significant reduction in attention. Attention deficit occurs maximally in hypoglycaemia.…”
Section: Discussionmentioning
confidence: 99%